Violence and mental illness: rethinking risk factors and enhancing public safety - Elbogen, Eric B. (Psychology and crime, 2023)
"When newsworthy violence occurs, mental illness is frequently blamed. This overemphasis on mental illness fuels social stigma and cognitive bias that exaggerates the link between violence and mental illness. But science shows this link is weaker than commonly believed and that numerous other risk factors are stronger predictors of violence, such as psychopathy, younger age, being male, access to guns, substance abuse, and anger. Because overemphasizing the role of mental illness leads to underemphasizing the role of these other risk factors, this leads to suboptimal violence prevention policy. Conversely, if the media, policymakers, and the public recognize these stronger, multiple risk factors for violence, then this opens up the door to developing and implementing more effective strategies for evidence-based violence prevention that will lead to greater public safety"--